From psychogeography to hanging‐out‐knowing: Situationist dérive in nonrepresentational urban research. Issue 2 (8th June 2018) - Pyyry, Noora
Abstract : Members of the Situationist International drifted in urban space on their dérives in the 1950s and 60s to grasp the city's "psychogeography." In this paper, I revisit the Situationist practice of drifting as part of doing nonrepresentational urban research on spatial justice in the city. In contrast to aiming for any fixed representations of a city's contours, I treat the dérive as a process of "becoming with": a continuous invention of the city (and the self) through ephemeral encounters. This understanding implies an emergent human subject, one that is changeable and creates breaks in knowledge via dwelling with other subjects (human, technological, architectural, etc.). Here, thinking is approached as a joint participation of the knowing human subject and the city, it is always spatial‐embodied. I have named this style of non‐linear reflection "hanging‐out‐knowing." Photography is connected to the dérive to direct attention to passing moments and banal details in the urban landscape: to tease out situations, or encounters, that may provoke the generative moment of enchantment. This experience can usually be detected only when it is already gone, but it forces a new perspective to the world. In doing research, this view does not open from practice alone, rather it is often inspired by theory. To illustrate the onto‐epistemological argument, I discuss a sound‐inspired photo‐walk in Vilanova i la Geltrú, a vibrant small city in the province of Barcelona.